On a method for approximate solving a backward stochastic differential equation - Zakharov, A.V. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2003)
A numerical method for solving a backward stochastic differential equation is described. The convergence proof for this method is based on the theorem on stability of solutions to such equations proved earlier by the author. The work was supported by the A.M. Lyapunov French-Russian Institute for Applied Mathematics and Informatics (grant 02-01).